Design and Implementation a Web-Based Semester Learning Plan Management Information System - Nike Sartika; Yuda Sukmana; Iik Abdul Kholik; Agus Ramelan (Universitas Sebelas Maret (UNS), 2023)
This research designs and implements an information system to manage web-based Semester Learning Plan using cloud computing technology, software, computers, and repositories as well as a serverless architecture. So far, the preparation of Semester Learning Plan in Department of Electrical Engineering UIN Sunan Gunung Djati Bandung is still done manually using a template in Microsoft Excel format. This method is considered ineffective because filling in takes a long time and the output is sometimes not uniform, both between lecturers and between courses. Based on this background, the author proposed the idea of creating a web-based Semester Learning Plan management information system. The method used to develop this system is the waterfall method which consists of five stages, namely requirements analysis, system and software design, implementation, testing, operation and maintenance. This information system using cloud computing technology and serverless architecture. The result of this research is a web-based Semester Learning Plan management information system. Through this system, lecturers no longer type manually into doc or xls format, but lecturers can directly input into the system or the web. The output is that the Semester Learning Plan can be downloaded and is in accordance with the applicable format and is in pdf format. The existence of this system can increase the effectiveness of lecturers in managing Semester Learning Plan.